The Effectiveness and Safety of Probiotic Supplements for Psoriasis: A Systematic Review and Meta-Analysis of Randomized Controlled Trials and Preclinical Trials - Liuting Zeng; Ganpeng Yu; Yang Wu; Wensa Hao; Hua Chen (Journal of Immunology Research)
Background. Patients with psoriasis need long-term medication to control their condition. Recent studies suggest that changing the intestinal flora may be a potential treatment. Methods. The databases were utilized to search the randomized controlled trials (RCTs) and preclinical trials about probiotic supplement in the treatment of psoriasis. The retrieval time is from the establishment of these databases to December 2020. RevMan5.3 was used for the risk assessment of bias and meta-analysis. This systematic review was registered in PROSPERO (CRD42021232756). Results. A total of 3 RCTs involving 164 participants were included. Two RCTs showed that probiotics can improve PASI and thereby improve the condition. For inflammation-related indicators, only one RCT showed that probiotics can improve the levels of CRP and TNF-α but have no obvious improvement effect on IL6. One RCT demonstrated the total effective rate of probiotics in the treatment of psoriasis. For adverse events, one RCT showed that the incidence of adverse events of probiotic treatment was low. Preclinical studies showed that continuous intervention with oral probiotics can significantly improve the progression of psoriasis and reduce the expression of inflammatory factors. The meta-analysis showed that the PASI between two groups was of no statistical significance (SMD 1.83 [-0.41, 4.07], P=0.11). Meanwhile, probiotics may improve skin thickness (SMD -5.87 [-11.34, -0.41], P=0.04) in animal model. Conclusion. Prebiotics may have a positive effect on alleviating the clinical symptoms of psoriasis, but a large sample of RCTs is still needed to support its therapeutic effect in psoriasis.